ANALYSIS OF LOVE IN “THE BROKEN WINGS” BY KAHLIL GIBRAN - Tira Nur Fitria (Jurusan Sastra Indonesia, 2022)
Love is a priceless gift and without it, life feels empty. Therefore, keep love with loyalty, honesty, and be able to keep our heart from being stained just for self-satisfaction which will regret in the end. This expression may as the basis for the writing of the novel